Perpaduan Syariah dan Budaya dalam Resolusi Konflik. - Koko Komaruddin (AHKAM : Jurnal Ilmu Syariah, 2016)
In harmonious and zero intolerance society, conflicts can still potentially occur. The cause of the conflict can be caused by many variables, such as politics, culture, religion, and economics. Research shows that in cases of multipurpose building, Hok Tek Bio temple, in Ciamis, the dominant factor of conflict is the different interpretation of the concept and implementation of sharia on houses of worship and diversity. Understanding sharia which puts theology as the basis of the diversity of the key religious figures of the Forum for Religious Harmony (FKUB) Ciamis, the Indonesian Ulama Council (MUI), and the local community around the temple become strong force to be conflict resolution. The combination of sharia values understanding of Muslim leaders in FKUB, MUI, and the community and the cultural values of the Sundanese people in Ciamis can play as togetherness bond in harmonious life. Therefore, the model of civic pluralism that combines sharia and culture as local wisdom becomes an effective conflict resolution model.DOI: 10.15408/ajis.v16i1.2900